CoQ10Phytosomes Improve Cellular Ubiquinone Uptake in Skeletal Muscle Cells: An Ex Vivo Study Using CoQ10-Enriched Low-Density Lipoproteins Obtained in a Randomized Crossover Study - Fabio Marcheggiani; Patrick Orlando; Sonia Silvestri; Ilenia Cirilli; Antonella Riva; Giovanna Petrangolini; Francesca Orsini; Luca Tiano (Antioxidants, 2023)
Coenzyme Q10 (CoQ10) bioavailability in vivo is limited due to its lipophilic nature. Moreover, a large body of evidence in the literature shows that muscle CoQ10 uptake is limited. In order to address cell specific differences in CoQ uptake, we compared cellular CoQ10 content in cultured human dermal fibroblasts and murine skeletal muscle cells that were incubated with lipoproteins from healthy volunteers and enriched with different formulations of CoQ10 following oral supplementation. Using a crossover design, eight volunteers were randomized to supplement 100 mg/daily CoQ10 for two weeks, delivered both in phytosome form (UBQ) as a lecithin formulation and in CoQ10 crystalline form. After supplementation, plasma was collected for CoQ10 determination. In the same samples, low density lipoproteins (LDL) were extracted and normalized for CoQ10 content, and 0.5 µg/mL in the medium were incubated with the two cell lines for 24 h. The results show that while both formulations were substantially equivalent in terms of plasma bioavailability in vivo, UBQ-enriched lipoproteins showed a higher bioavailability compared with crystalline CoQ10-enriched ones both in human dermal fibroblasts (+103%) and in murine skeletal myoblasts (+48%). Our data suggest that phytosome carriers might provide a specific advantage in delivering CoQ10 to skin and muscle tissues.